Electrochemistry for Biofuel Generation: Transformation of Fatty Acids and Triglycerides to Diesel‐Like Olefin/Ether Mixtures and Olefins. Issue 5 (3rd February 2015) - R. dos Santos, Tatiane; Harnisch, Falk; Nilges, Peter; Schröder, Uwe
Abstract Electroorganic synthesis can be exploited for the production of biofuels from fatty acids and triglycerides. With Coulomb efficiencies (CE) of up to 50 %, the electrochemical decarboxylation of fatty acids in methanolic and ethanolic solutions leads to the formation of diesel‐like olefin/ether mixtures. Triglycerides can be directly converted in aqueous solutions by using sonoelectrochemistry, with olefins as the main products (with a CE of more than 20 %). The latter reaction, however, is terminated at around 50 % substrate conversion by the produced side‐product glycerol. An energy analysis shows that the electrochemical olefin synthesis can be an energetically competitive, sustainable, and—in comparison with established processes—economically feasible alternative for the exploitation of fats and oils for biofuel production.